(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The present research was carried out on the adaptation and yield of Glycine Max l., in the agroecological conditions of the Quinindé canton of Ecuador, under the geographical coordinates: 00o13’33’’ north latitude and 73o26’00’’ west longitude, to determine the adaptation and yield of 15 soybean materials to these agroecological conditions. Fifteen treatments and three replications were applied, using InfoStat software for significance testing. In the experiment, soil analysis, mechanized field preparation, sowing, weed control, fertilization, phytosanitary controls and harvesting were carried out. The agronomic parameters evaluated were: plant height, branches per plant, days to flowering, bearing height, pods per plant, days to maturity, days to harvest, seeds per pod, seeds per plant and economic analysis. The results indicate a good adaptation of all treatments; specifically their earliness, loading height, grain weight and yield. It is concluded that the adaptation and yield processes will contribute significantly to the formulation of new studies, considering the growing demand for products made from soybeans, thus benefiting producers and consumers.